Educational level and employment status in adults with congenital heart disease. (13th September 2017) - Pfitzer, Constanze; Helm, Paul C.; Rosenthal, Lisa-Maria; Walker, Christoph; Ferentzi, Hannah; Bauer, Ulrike M. M.; Berger, Felix; Schmitt, Katharina R. L.
Abstract: Purpose: Through this study we aimed to assess the educational level and employment status of adults with CHD in Germany. Methods: Data were acquired from an online survey carried out in 2015 by the German National Register for Congenital Heart Defects. A total of 1458 adults with CHD participated in the survey (response rate: 37.6%). For 1198 participants, detailed medical information, such as main cardiac diagnosis and information from medical reports, was available. Results: Of the participants surveyed (n=1198), 54.5% (n=653) were female, and the mean age was 30 years. The majority of respondents (59.4%) stated that they had high education levels and that they were currently employed (51.1%). Patients with simple CHD had significantly higher levels of education (p<0.001) and were more likely to be employed (p=0.01) than were patients with complex CHD. Conclusions: More than half of the participants had high education levels and the majority were employed. The association between CHD and its severity and individuals' educational attainment should be investigated more closely in future studies.